Optimization of Literacy, Numeracy, and Technology Adaptation through the Implementation of the Kampus Mengajar Program - Sinta Ulina Situmorang (Jurnal Pendidikan Vokasi Indonesia, 2024)
Improving literacy and numeracy at the primary education level is a crucial aspect that must be prioritized in the context of national educational development. One of the initiatives to enhance students' literacy and numeracy skills in Indonesia is the "Kampus Mengajar" Program, a part of the Merdeka Belajar Kampus Merdeka (MBKM) policy implemented by the Ministry of Education, Culture, Research, and Technology. SDN 101914 Kampung Baru, as a primary educational institution, plays a significant role in shaping students' character and foundational skills. This study aims to analyze the implementation of the Kampus Mengajar Batch 6 Program in improving literacy, numeracy, and technology adaptation at SDN 101914 Kampung Baru. The research method followed the structured stages outlined in the Kampus Mengajar Batch 6 guideline, involving university students as agents of change within the school environment. The findings indicate that the program had a significant positive impact on enhancing students' literacy, numeracy, and technology adaptation skills.